Cost-effectiveness of a mentalisation-based treatment for antisocial personality disorder in males convicted of an offence on community probation in England and Wales: Multicentre, assessor-blind randomised controlled trial - Barbara Barrett; Elizabeth Simes; Karen Yirmiya; James M. S. Wason; Alison Frater; Angus Cameron; Stephen Butler; Zoe Hoare; Mary McMurran; Paul Moran; Mike Crawford; Stephen Pilling; et al. (PLoS ONE, 2026)
This study addresses a critical gap in the evidence base for cost-effective psychological interventions for antisocial personality disorder (ASPD) in forensic settings by presenting a full trial-based economic evaluation of mentalisation-based treatment plus probation as usual (MBT-ASPD + PAU), compared to PAU alone, for males with ASPD convicted of an offence in England and Wales. The economic evaluation adopted a societal perspective, incorporating costs to health care, the criminal justice system, and the wider societal impact of offending. Outcomes were assessed 24 months post-randomisation. The primary cost–utility analysis compared costs with quality-adjusted life years (QALYs) derived from the EQ-5D-5L, while a secondary cost-effectiveness analysis compared costs with aggression outcomes measured by the Overt Aggression Scale – Modified (OAS-M). Although missing data limited definitive conclusions regarding service use, available data suggest that participants in the PAU group spent more time in custody than those in the MBT-ASPD + PAU group. Utility scores and quality of life showed minimal variation over follow-up, with no significant differences between groups. Overall costs were lower in the MBT-ASPD + PAU group, though not statistically significant. Over the 24-month period, MBT-ASPD + PAU was associated with both reduced costs and lower aggression (as reflected in OAS-M scores), indicating that each unit reduction in aggression yielded a cost saving of approximately £93. For QALYs, MBT-ASPD + PAU appeared cost-effective compared to PAU across all values a decision-maker may be willing to pay for improvements in outcome. These findings provide preliminary evidence for the potential economic value of MBT-ASPD + PAU in a forensic ASPD population, particularly in relation to aggression reduction and the associated cost savings. Trial registration This trial is registered with ISRCTN (ISRCTN 32309003).